O ambiente de aprendizagem do ensino de graduação em administração da região nordeste do Brasil - Lima, Thales Batista de (2015)
This study had as objective to analyze the dimensions of the teaching learning environment in Administration in the Northeast of Brazil in the administrator formation process. To achieve this purpose, the following specific objectives were established: a) identify the historical trajectory Administration undergraduate teaching northeastern Brazil from the reporting teachers who participated in the creation process of these courses; b) to characterize the dimensions of the administrator formation of the learning environment; c) discuss the influences on education in Business Administration in the Northeast from the learning environment dimensions; d) Propose guidelines for regionalized training administrator. Therefore, it approached the context of formation of administrators in the Northeast. Then, there was a historical Administration in undergraduate education in the Northeast, emphasizing adherence to teaching models for American business and developmental perspective. Still, there is a curriculum of courses in the region and discusses the dimensions of the learning environment, highlighting the following: historical-political, structural and institutional, cultural, social and technological-virtual. It also discusses the significance of the agents involved in promoting a qualified education, namely students, teachers, managers and practical, beyond the important role of government, universities and other institutions. The participants were nine teachers involved with the creation and development of the Administration course in the region. The interviews were transcribed and coded, and subsidize the categorization of discourse divided in the first three dimensions presented. The review process was guided by the interpretative paradigm and adopted a qualitative approach, since the theme of the discussion was built from the reports of interviewed teachers, of which emerged categories that relate to each other through the dimensions focused at work. The results showed that the dimensions of the learning environment effectively play a leading role in teaching Administration. The current situation results from a historical trajectory, permeated by conflicts and political interests, not only at national, but also regional or universities. The physical structure and institutional support to the promotion of a qualified education are among the most prominent factors in qualified training. Still, the cultural and social perspective impacts on the quality of education in Administration, where it is, the knowledge about the peculiarities of the regional context. The use of technological resources can assist the process of teaching and learning, if used taking into account the suitability to the conditions available and own use by organizational forms in the region. The identity of the course, teaching, and administrator still is pervasive not only internally, but also to society at large, necessitating an effective action of the Federal and Regional Councils and for the regulation and delimitation administrator characteristic professional context. In this sense, this thesis proposes some guidelines contextual, culminating in actions that can facilitate teaching in Management through a more regional training from the dimensions of the local learning environment. Finally, it is concluded that a regionalized training is in an alternative to promote closer ties between teaching and learning environment in order to align themselves with the possibilities of professional experience in management in the Northeast.